Bridging CA and EA: Understanding Cross-Linguistic Influence on Learners’ Structural Errors - Nadila Tanjung; Hafifah Hasyanah Dalimunthe; Tuti Alawiyah Ramadhani Nasution; Airen Widyana; Siti Ismahani (Jurnal Pendidikan dan Sastra Inggris, 2024)
This study investigates learner errors through a non-contrastive error analysis approach to identify the linguistic, cognitive, and instructional factors shaping English language performance. Drawing on Richards’ (1971) framework, the research analyzes errors found in students’ written compositions to categorize them into intralingual, developmental, and performance-based types. Using qualitative descriptive methods, 60 EFL learners were asked to produce short academic paragraphs, which were subsequently examined through systematic coding and classification. The findings reveal that intralingual errors particularly overgeneralization, incomplete rule application, and confusion of structures dominate the learners’ output, indicating internal learning processes rather than L1 interference as the primary difficulty source. Developmental errors also emerge, reflecting learners’ transitional stages as they internalize new grammar rules. Performance errors, though less frequent, are attributed to momentary lapses in attention and limited automaticity. The study highlights the pedagogical significance of focusing on learners’ developmental patterns instead of solely comparing L1–L2 structures. The results underscore the need for targeted instruction emphasizing form–meaning connections, clear feedback strategies, and opportunities for reflective revision. Overall, the research provides empirical evidence supporting the usefulness of non-contrastive error analysis in understanding learner interlanguage and informing more responsive classroom practices.